Observaciones generales sobre la ejecucion de programas de mejoramiento genetico de la yuca en America Latina - Hershey, Clair H. (International Center for Tropical Agriculture, 1991)
The importance of appropriate genetic variability for plant breeding work in cassava is highlighted; genetic erosion has been slight and therefore efforts should be made to collect and maintain germplasm of both cultivated and wild species. It is necessary to carry out physiological studies aiming at the control of floral initiation in cassava and to explore other breeding methods such as recurrent selection, self-pollination, and selection within and between S1 progeny. The different cassava environments should be classified and grouped in order in define breeding objetives adequately. Currently, selection criteria are focussed toward adaptation to the agroecosystem, morpholoigical characteristics, potential to improve physiological processes (LAI, HI, photosynthesis) and quality factors of cassava for the different markets. The role of biotechnology as a tool for plant breeders is discussed; the most immediate application of biotechnology in cassava is in the conservation, exchange, and characterization of germplasm. Future applications can be in the field of genetic engineering to eliminate HCN from materials or incorporate other desirable genes for the production of toxins conferring resistance to insects. From the initial stages of screening, plant breeders should be aware of the conditions and needs of target farmers to assure successful technology transfer. The objectives of germplasm exchange should be clearly defined and basic information should be provided on climate, soils, prevalent pests and diseases, etc. Training activities in the the validation and transfer of new technology should be enhanced; likewise, the assessment of materials should not be based on yield alone; production, processing, and marketing data should also be considered. (CIAT)